2016
DOI: 10.1246/bcsj.20160391
|View full text |Cite
|
Sign up to set email alerts
|

C–H Borylation by Platinum Catalysis

Abstract: Herein, we describe the platinum-catalyzed borylation of aromatic CH bonds. N-Heterocyclic carbene-ligated platinum catalysts are found to be efficient catalysts for the borylation of aromatic C(sp 2 )H bonds when bis(pinacolato)diboron is used as the boron source. The most remarkable feature of these Pt catalysts is their lack of sensitivity towards the degree of steric hindrance around the CH bonds undergoing the borylation reaction. These Pt catalysts allow for the synthesis of sterically congested 2,6-disu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 124 publications
(15 reference statements)
0
17
0
Order By: Relevance
“…Mechanistically, the authors demonstrated that dvtms dissociates from the metal center (Scheme 88). 198 It was proposed that the coordinatively unsaturated Pt−NHC complex reacts with B 2 pin 2 to give [Pt(NHC)(Bpin) 2 ], followed by C(sp 2 )−H activation via σ-bond metathesis or oxidative addition to give Pt(IV).…”
Section: Platinum−nhc Complexesmentioning
confidence: 99%
“…Mechanistically, the authors demonstrated that dvtms dissociates from the metal center (Scheme 88). 198 It was proposed that the coordinatively unsaturated Pt−NHC complex reacts with B 2 pin 2 to give [Pt(NHC)(Bpin) 2 ], followed by C(sp 2 )−H activation via σ-bond metathesis or oxidative addition to give Pt(IV).…”
Section: Platinum−nhc Complexesmentioning
confidence: 99%
“…Although most of this type of C–H borylation processes have been carried out using rhodium and iridium systems, 4 there have been a few reports on the utilization of platinum complexes for the formation of C–B bonds, either in stoichiometric reactions or in catalytic processes. 5 Turculet and Stradiotto reported the dehydrogenative coupling of B–H/C–H bonds at a Pt( ii ) center, 5 a whereas Chatani, Tobisu et al suggested the participation of σ-BH complexes in the platinum-catalyzed borylation of arenes. 5 b , c However, the interaction of tricoordinated hydroboranes with platinum centers leading to σ-BH complexes has proven elusive.…”
Section: Introductionmentioning
confidence: 99%
“…N-Heterocyclic carbene complexes of copper and platinum possessing an acenaphthylene backbone subunit have been marginally reported to date [53,70,97], but have found catalytic applications.…”
Section: Nhc-bian-cu and Nhc-bian-ptmentioning
confidence: 99%
“…Literature reports on NHC-BIAN-Pt complexes cover only a single example. In 2016, Tobisu and co-workers [97] published a synthesis of the platinum N-heterocyclic carbene complex 113 by the reaction of NHC precursor 4g with Karstedt's complex, yielding complex 113 in 36% yield (Scheme 45). The authors reported high catalytic activity of platinum complex 113 in the C-H activation/borylation reaction of 1,3-dimethyl-5-tertbutylbenzene (112), affording arylboronic ester 40b in 72% yield.…”
Section: Nhc-bian-cu and Nhc-bian-ptmentioning
confidence: 99%